Modified fertilization strategies to increase grain protein of soft red winter wheat in the Mid‐Atlantic region - Nicole M. Fiorellino; Louis A. Thorne (Agrosystems, Geosciences & Environment)
Abstract Millers in the Mid‐Atlantic are seeking high protein content in their flour and they are currently shipping hard wheat produced in the Western United States to blend with soft red winter wheat (SRWW) (Triticum aestivum L.) produced locally to achieve this. They may offer a premium for a local source of SRWW with higher grain protein. This may be achieved through selection of SRWW varieties with high protein potential, modifying nitrogen (N) fertilizer management through timing or total N rate, or the combination of both. We hypothesized that grain protein of SRWW varieties with either high yield or high protein potential could be increased with late‐season N application at the same rate and the increased protein result in decreased grain yield. Four fertilization strategies that shifted the same total N later in the season, that included a post‐flowering N application, and one that increased the total N rate were evaluated along with three varieties selected for high grain protein potential and one high‐yielding variety. Both grain yield and grain protein were significantly affected by variety, and grain protein only was significantly affected by fertilizer treatment. Shifting the same total N rate to four applications from three increased grain protein but was not different than four applications at an increased N rate. A significant, inverse relationship between grain yield and protein was observed. Producers in the Mid‐Atlantic are encouraged to calculate their cost of production and weigh this against possible protein premiums prior to production of high‐protein wheat.